Biomimetics: Conductive and Stretchable Adhesive Electronics with Miniaturized Octopus‐Like Suckers against Dry/Wet Skin for Biosignal Monitoring (Adv. Funct. Mater. 52/2018). (27th December 2018) - Chun, Sungwoo; Kim, Da Wan; Baik, Sangyul; Lee, Heon Joon; Lee, Jung Heon; Bhang, Suk Ho; Pang, Changhyun
Abstract : In article number1805224, Changhyun Pang and co‐workers report skin‐attachable and water‐resistant stretchable electronics that are fabricated by employing an array of octopus‐like patterns on conductive polymer composite films. The electronic patch is not only highly sensitive to strain and pressure, but also strongly adhesive on dry and wet surfaces due to the suction effect. The device demonstrates measurements of biosignals and bending motions in underwater environments.